2016
DOI: 10.1007/s10047-016-0923-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between driveline features and driveline infection in left ventricular assist device selection

Abstract: Although the survival rate for left ventricular assist device (LVAD) therapy has improved, device-related complications are an unpredictable threat to the patient's quality of life. We focused on driveline infection, and aimed to determine whether specific features of drivelines affect the frequency of infection. We enrolled patients who underwent LVAD implantation and were followed-up at our institute between 2007 and 2015. We counted the occurrences of driveline infection requiring any antibiotic therapy ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…The HMII driveline had only 20%-25% of stiffness compared to other devices (EVAHEART and DuraHeart) and the highest driveline infection-free rate among those three devices. 22 In addition, the HMII driveline is only made of soft silicone, whereas the more rigid materials polyurethane + silicone used in the HM3 and the polyurethane material in the HVAD driveline potentially lead to more trauma and force applied to the driveline exit site during activities of daily living such as changing clothes, showering, changing bags, etc or unintentionally while sleeping or more generally through the behavior of each patient and the management of Despite the different relative risks for DLI readmission depending on the device, most likely due to device-specific driveline characteristics, the device type was not a significant risk factor for 2-year survival after HMII, HM3 or HVAD implantation (P = .26) (Table 5). Further investigations should be performed to investigate the influence of driveline materials and their mechanical properties as a risk factor for DLIs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HMII driveline had only 20%-25% of stiffness compared to other devices (EVAHEART and DuraHeart) and the highest driveline infection-free rate among those three devices. 22 In addition, the HMII driveline is only made of soft silicone, whereas the more rigid materials polyurethane + silicone used in the HM3 and the polyurethane material in the HVAD driveline potentially lead to more trauma and force applied to the driveline exit site during activities of daily living such as changing clothes, showering, changing bags, etc or unintentionally while sleeping or more generally through the behavior of each patient and the management of Despite the different relative risks for DLI readmission depending on the device, most likely due to device-specific driveline characteristics, the device type was not a significant risk factor for 2-year survival after HMII, HM3 or HVAD implantation (P = .26) (Table 5). Further investigations should be performed to investigate the influence of driveline materials and their mechanical properties as a risk factor for DLIs.…”
Section: Discussionmentioning
confidence: 99%
“…First, the HM3 has the largest driveline diameter of the outer (extracorporeal) pump cable (6.1 mm), compared to the HMII (5.7 mm) and HVAD (4.6 mm). Second, Imamura et al in 22 showed that driveline stiffness could be an important factor in the context of DLI. The HMII driveline had only 20%‐25% of stiffness compared to other devices (EVAHEART and DuraHeart) and the highest driveline infection‐free rate among those three devices 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HeartMate II VAD and HeartWare HVAD were parallel in developing driveline infections in the studies by Haglund et al, (2015) and Stulak et al, (2016) [ 15 , 26 ]; other studies reported a lower incidence of driveline infections in patients with a HeartWare HVAD relative to that with a HeartMate II VAD [ 36 , 85 , 86 ]. The difference in the incidence of driveline infections between VADs from different manufacturers is possibly due to their differences in driveline flexibility, cable diameters and other driveline characteristics such as biomaterials used for driveline manufacturing [ 36 , 87 ]. Smaller outer diameter and lower stiffness of drivelines have been associated with less driveline infections [ 87 ].…”
Section: Prevention Of Vad-specific Infectionsmentioning
confidence: 99%
“…The difference in the incidence of driveline infections between VADs from different manufacturers is possibly due to their differences in driveline flexibility, cable diameters and other driveline characteristics such as biomaterials used for driveline manufacturing [ 36 , 87 ]. Smaller outer diameter and lower stiffness of drivelines have been associated with less driveline infections [ 87 ]. Though there is a lack of information in the literature comparing different materials of the drivelines as predictors of driveline infections, studies on other implantable medical devices such as central venous catheters found that the nature of the biomaterials was one of the key determinants of device-related infections [ 88 , 89 , 90 ].…”
Section: Prevention Of Vad-specific Infectionsmentioning
confidence: 99%